Pelagic ecosystem connectivity and risk assessment applied to Marine Spatial Planning in the Gulf of Cadiz, Cape of Gata and Alboran Sea - Muñoz Muñoz, María (UMA Editorial, 2019)
This thesis aims to consider the pelagic ecosystem and risk assessment in Marine Spatial Planning (MSP) of the Alboran Sea. Biological oceanography has to be set in MSP approaches and results have to be expressed in an appropriate format for decision makers. In this context, the first manuscript of the thesis, shows a methodology to regionalise surface waters, which can be used to identify different management units and GAP analysis for Marine Protected Area (MPA) network design. Furthermore, surface connectivity through geostrophic currents is shown and essential connections among basins and coasts are expressed in travel days, providing useful information for MPA network or coastal risk assessment. The second manuscript shows fertilising processes associated with submarine canyons and vertical connectivity from the surface to deep water (and vice versa) by daily vertical migration of zooplankton. Thus, surface and deep-sea ecosystems are connected on a daily scale, which should be considered in MSP and environmental impact estimation of industrial effluents. The third manuscript shows fertilising processes associated with submarine seamounts and fronts, where local productivity above seamounts remain in the study area and could enhance benthic diversity and target species. The hydrodynamic and bathymetric characteristics of the zone serve as a base for a MPA proposal and are discussed in a widespread framework in order to establish a transboundary management program from land to deep-sea around the Cape of Gata. The fourth manuscript focuses on spatial risk assessment of present and upcoming human uses of the sea in European hake nursery areas. The vulnerability analysis of EUNIS habitat to cumulative pressures reveals Malaga Bay as being the most vulnerable nursery area therefore a fishery reserve is suggested.
Conflicts among uses in the north Alboran sea were higher between MPAs and trawling activity. Future scenarios considering the increase of renewable energy and alternative food production show conflicts between aquaculture and MPAs as well as offshore wind farms and offshore shipping. These results present strong reasons for implementing an integrated spatial management approach, including benthic trawling in the north Alboran Sea. The applied spatially assessment framework is transparent and transferable to other Mediterranean regions. Fecha de lectura de Tesis Doctoral:
Keywords: Ecología; Oceanografía; Marine Spatial Planning; Pelagic Ecosystem; Connectivity; Alboran Sea; Gulf of Cadiz